Communication Therapy in Stroke Patients with Aphasia: A Narrative Review - Sally Syamima; Urip Rahayu; Nur Oktavia Hidayati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: Stroke is the number one cause of death in Indonesia. The stroke had some effects. One of the common complications is aphasia. Aphasia is a disorder of speaking, understanding what others said, and even the ability to read and write too. This can lead to communication problems in a stroke patient. Communication therapy is one of the most effective ways to treat aphasia. Objective: The aim of this article is to find out the types of communication therapy for stroke patients who suffered with aphasia. Methods: We conducted a review and collected the articles by searching several databases such as PubMed, Science Direct, and CINAHL. We also used search engines such as Google Scholar. After the articles are obtained, the articles will be sorted by keywords. The keywords used were stroke patient OR post-stroke AND communication therapy OR language therapy OR speech therapy AND aphasia OR aphasic. Then, the articles are sorted by inclusion and exclusion criteria. After obtaining appropriate articles, the articles were analyzed by using thematic analysis. Results: The search resulted in 708 articles. After several selection steps, 23 articles were analyzed, and seven types of communication interventions were found that can be applied to stroke patients who suffered aphasia.  Conclusion: The results of a review of all articles show that there are various types of communication therapy that can be given to stroke patients who experience aphasia. The therapy is grouped into 7 types of therapy, which include Constraint Induced Aphasia Therapy, Electronic-based therapy, Melodic Intonation Therapy, Intensive Therapy, Augmentative and Alternative Communication, Cognitive Therapy, and AIUEO. Suggestion: Furthermore, researchers can conduct a systematic review related to which communication therapy is the most effective for treating aphasia, especially in stroke patients.